The role of intraalveolar fibrosis in the process of pulmonary structural remodeling in patients with diffuse alveolar damage. - Fukuda, Y. (1987)
For a study of the processes and mechanisms of pulmonary structural remodeling in fibrotic lungs and metaplastic squamous epithelial cells in fibrotic alveoli, immunohistochemical, ultrastructural, and light-microscopic morphometric observations were made of the lungs in acute and proliferative stages of diffuse alveolar damage (n = 40) obtained from biopsies and autopsies. Morphometry showed that intraalveolar fibrosis developed in the early proliferative stage and was more prominent than interstitial fibrosis. In the early proliferative stage, activated myofibroblasts migrated into intraalveolar spaces through gaps in the epithelial basement membrane. They then attached to the luminal side of epithelial basement membrane and produced intraalveolar fibrosis and coalescence of alveolar walls. This intraalveolar fibrosis was the essential factor in the remodeled lungs. Albumin, fibrinogen, immunoglobulins, and surfactant apoprotein were present throughout the hyaline membrane. Fibronectin was not found in hyaline membrane of the lesions in early acute stage but was demonstrated in later stages in outer layers of hyaline membranes and in the areas of intraalveolar fibrosis. Fibronectin may be responsible for the migration and proliferation of myofibroblasts in intraalveolar spaces. Metaplastic single-layered and stratified squamous epithelial cells were keratin-positive and surfactant apoprotein-negative. These metaplastic epithelial cells were frequently found in the alveoli with minimal Type II epithelial cell proliferation and in the grossly scarred alveoli.